2013
DOI: 10.1590/s2179-83972013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Factibilidade, segurança e eficácia do fechamento percutâneo da comunicação interatrial em crianças pequenas

Abstract: Introdução: A experiência com o fechamento percutâneo da comunicação interatrial (CIA) em crianças pequenas é limitada. Avaliamos a factibilidade, a segurança e a eficácia desse procedimento em crianças com peso < 20 kg. Métodos: Estudo descritivo observacional de uma coorte de crianças < 20 kg submetidas a tratamento percutâneo. Pacientes com dilatação ventricular direita e sintomas evidentes foram in cluídos. Implantamos próteses aprovadas pela ANVISA, sob monitorização ecocardiográfica transesofágica. Os pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Our experience is similar to that of Ribeiro et al 6 . We recently published our data regarding device closure of ASDs in children < 4 years old.…”
Section: See Page 165supporting
confidence: 92%
See 2 more Smart Citations
“…Our experience is similar to that of Ribeiro et al 6 . We recently published our data regarding device closure of ASDs in children < 4 years old.…”
Section: See Page 165supporting
confidence: 92%
“…Abolition of a left to right shunt has been shown to improve lung function in children with bronchopulmonary dysplasia, even allowing ventilator-dependent patients to be successfully extubated. [3][4][5] In the current issue of Revista Brasileira de Cardiologia Invasiva, Ribeiro et al 6 have reported on transcatheter closure of ASDs in children weighing less than 20 kg. Theirs is a vast experience, totaling 80 patients over a span of 15 years, and utilizing a wide variety of devices.…”
Section: See Page 165mentioning
confidence: 99%
See 1 more Smart Citation